A NURBS boundary-only approach in elasticity - Mallardo, Vincenzo; Ruocco, Eugenio (European Journal of Computational Mechanics, 2016)
An improvement to the classical application of the isogeometric approach to the two-dimensional boundary element method is proposed. In the classical isogeometric approach the boundary conditions are imposed directly to the control variables that are not always interpolatory of the governing variables, thus introducing an error that may also be large. The issue has been debated in the finite element method context where it has recently motivated various alternative techniques, but it is still open in other numerical methods. In the present paper the approach, introduced by the authors in a previous paper, to correctly impose any general boundary condition in the boundary element method framework, is theoretically and numerically investigated. Comparison with analytical solutions, classical boundary element solutions and isogeometric boundary element solutions are carried out to demonstrate the improved performance of the proposed approach.